Pelaksanaan Langkah-Langkah Positioning Produk Bawang Goreng Inovatif Pada MDN-Crispy 22 - Ichwannul Muslimin (Jurnal Niaga & Bisnis (e-journal), 2015)
In the Middle of competition and business at the moment trying to increase market share and to increase sales volume.Crispy Mdn-22 want to target a wider market segment. Segment of the market you want to target by-Crispy Mdn 22 is the entire market segment of society in North Sumatra and businesses that require culinary fried onions as a flavor enhancer in food. This research is qualitative descriptive approach. The technique of collecting data using interviews and documentation. Informants in this study are business owners and employees Crispy Mdn-22. Analysis of the data used in this research is descriptive qualitative analysis. The purpose of this study was to determine the steps set the product positioning of crispy fried onions Crispy Mdn-22.The results showed that the steps of positioning measures undertaken by Crispy Mdn-22 is to define the relevant product market and the market as you wish, Make management of product standards, determine the evaluation standards, determines the type of service, define the distribution channel, plan and implement the positioning strategy.Advice can be given in this study isto improve effectiveness in distribution activities it would require an increase of facilities and supporting infrastructuredistribution activities and to enlarge the market of Crispy Mdn-22, then Crispy Mdn-22 need to carry out the activities of the marketing mix . Key Words      : Steps, Positioning